Review Of The Implementation Of The Electronic Medical Record System In Health Facility Services Based On The Regulation Of The Minister Of Health Number 24 Of 2022 Concerning Medical Records - Ayus Fajar Asrofi; Erikson Sihotang; Ni Ketut Wiratny (International Journal Labs, 2024)
The implementation of electronic medical records in health facility services based on the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 imposes an obligation on all health service facilities to maintain electronic medical records, including independent practice places run by health workers and medical personnel. The Ministry of Health can impose administrative sanctions or written warnings as well as recommendations for revoking or revoking accreditation status on health service facilities that commit violations. According to Article 32 of Minister of Health Regulation Number 24 of 2022, the contents of medical records are kept confidential by all parties involved in health services. These parties are health workers who provide health services, leaders of Health Service facilities, personnel related to the financing of Health services (insurance parties), pupils or students who are in charge of treatment and/or information management in Health Service facilities and other parties who have access to patient health data and information in Health Service facilities.